2001
DOI: 10.2166/ws.2001.0065
|View full text |Cite
|
Sign up to set email alerts
|

Assessing pathogen removal efficiency of microfiltration by monitoring membrane integrity

Abstract: This study was conducted to investigate the ability of various methods of monitoring membrane integrity to respond to changes in actual membrane integrity imposed by the compromised fibers within the microfiltration unit. In addition, the pilot-scale MF unit was challenged with high concentrations of coliform, Cryptosporidium, and spore, in order to assess the pathogen removal capability of microfiltration. A correlation between the integrity tests and microbial challenge data was also made. The integrity test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Microfiltration log removal values of 4.6 ± 0.96 were reported by Hong et al [31] for Cryptosporidium from a pilot-plant with 0.2 µm nominal pore size polypropylene filter in Tampa, Florida. This is consistent with a 4–7 log removal range reported by Reardon et al [53] for protozoa.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Microfiltration log removal values of 4.6 ± 0.96 were reported by Hong et al [31] for Cryptosporidium from a pilot-plant with 0.2 µm nominal pore size polypropylene filter in Tampa, Florida. This is consistent with a 4–7 log removal range reported by Reardon et al [53] for protozoa.…”
Section: Methodsmentioning
confidence: 73%
“…For the DPR advanced treatment processes, microfiltration (MF), reverse osmosis (RO), UV, ozone, biological activated carbon filtration (BAC or BAF), membrane bioreactors (MBR), and nanofiltration (NF) were the processes considered. Microfiltration log removal values of 4.6 ± 0.96 were reported by Hong et al [ 31 ] for Cryptosporidium from a pilot-plant with 0.2 µm nominal pore size polypropylene filter in Tampa, Florida. This is consistent with a 4–7 log removal range reported by Reardon et al [ 53 ] for protozoa.…”
Section: Methodsmentioning
confidence: 73%
“…Because the membranes used to purify drinking water have pores that are smaller (typically 0.04-0.2 μm) than microorganisms (typically 0.5-5.0 μm), microorganisms are effectively rejected through a sieving mechanism (30), although some microorganisms (e.g., ultramicrobacteria (28)) can pass through the membranes. However, defects on a membrane's surface can decrease sieving efficiency, allow pathogens to pass through the membrane, and affect public health, and it is important to test the integrity of membranes during the filtration process (1,9,10). A membrane integrity test is frequently conducted by counting particles in filtered water and/or checking pressure-induced decay by applying high pressure to the membranes.…”
mentioning
confidence: 99%
“…What is not clear is whether the fouling layer reduces the sensitivity or reliability of direct integrity tests in signaling a breach of membrane integrity. However, a recent study showed that membrane fouling had little to no effect on the sensitivity of pressure decay and diffusive airflow tests (Hong et al, 2001). Nonetheless, further work should be conducted to verify this finding.…”
Section: Direct Integrity Monitoring Techniquesmentioning
confidence: 99%
“…A more recent study (Hong et al, 2001) attempted to establish correlations between microbial removal efficiency of a pilot‐scale microfilter and results of direct integrity monitoring tests (pressure decay and diffusive airflow tests). Cryptosporidium spp.…”
Section: Direct Integrity Monitoring Techniquesmentioning
confidence: 99%